Russianisms in Contemporary English Online Media - L.K. Khalitova (Ученые записки Казанского университета: Серия Гуманитарные науки, 2016)
In this study, the use of Russian borrowings (Russianisms) in English (both British and American) online mass media (newspapers) has been described. Foreign and Russian linguists have shown the persistent interest in borrowings. However, the latest literature indicates a lack of research works describing the current state of Russianisms in English periodicals. The aim of this research is to describe Russianisms in contemporary English online periodicals. We have used the continuous sampling method in order to select Russianisms of different semantic groups, as well as both quantitative and qualitative methods to analyze the frequency and context of their use. The language resources have come from the texts of contemporary English online media (The New York Times, The Times, The Sunday Times, and The Guardian) over the period from 2010 to 2016 (25 177 articles). According to this research, the most numerous group of Russianisms is the vocabulary of the Soviet reality – Sovietisms – (12 583 articles) and the socio-political vocabulary (12 548 articles). This proves the significant impact of great historical events on the language development. The newspaper articles analysis has suggested that Russianisms represent not only various concepts and realities of the Russian culture and history. Russian borrowings from the household vocabulary (troika, matryoshka), sociopolitical lexicon (tsar/czar), and Sovietisms (gulag) can occur in contexts unrelated to the Russian history or culture. This demonstrates that Russianisms are acquiring new meanings and losing their specific cultural or national features due to assimilation.